Student’s Science Literacy in Science Learning at Elementary School - Rizky Cahyaningtyas; Anatri Desstya (Lectura : Jurnal Pendidikan, 2024)
This study aims to describe literacy in science learning in elementary schools. This study uses a type of qualitative research. This research was conducted at SDN 1 Karangsari which is located in Karangsari Village, Kec. Rowosari, Kab. Kendal, Prov. Central Java with postal code 51354. This analysis makes use of both primary and secondary sources of information. Interviews, observations, and field notes are all tools used in data collection. Methods for gathering data, reducing it, presenting it, and drawing conclusions from it. Use data triangulation to verify the accuracy of your findings. The conclusion of this study is that scientific literacy in science learning at SDN 1 Karangsari has been instilled. With reference to indicators, identify and explain scientifically valid phenomena (about blood circulation), evaluate and design investigations (about the properties of light), interpret data and conclusions based on scientific evidence (about the occurrence of rainbows).